Biotopes of national nature park “Podilski Tovtry” (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
Today information about biotopes for conservation of flora and vegetation becomes more and more important. Territory of National Natural park "Podilski Tovtry" is located on the verge of European deciduous forests and the Eurasian steppe areas. Prevailing territories are reclamation of land. The insignificant areas of natural and seminatural landscapes are covered by a plant cover (forest, meadows, meadows- steppe, steppe, lime-stones, bogs, water-fringe and water communities). The biotopes of NNP are given in accordance with a classification chart for the forest and forest-steppe zones of Ukraine. The quantitative indexes of different levels of biotopes of different classifications, that are used in Europe, are compared . The results of analysis of types of biotopes of NNP are described. The places of distribution of separate valuable biotopes are specified.
Keywords: NNP Podilski Tovtry, biotopes, ecosystems, classification.